Learning for or Learning with: Avaliar se Avaliando for an ELT Assessment Otherwise - Haus, Camila; Schmicheck, João Victor (Íkala, Revista de Lenguaje y Cultura, 2022)
We are two teachers engaged with English language teaching (ELT) from a critical perspective. As many other instructors who share this same line of thought, we have felt discomfort throughout our careers when evaluating students. Students, in turn, have also experienced the triggering of emotions, such as insecurity and imposterism when facing a test. This happens because there is still a predominance of structuralist, modern, and positivist assumptions in teaching, and more evidently, in assessment. With this background, we turned our attention to assessment in a more critical way, trying to develop a project that challenged the traditional, hegemonic, and normative paradigms in elt and proposed an alternative otherwise. This is how, at a language center from a Federal University in Brazil, we decided to explore a different way of doing assessment by asking students to collaboratively create booklets during one semester. In this article, we present and reflect on the approach we took. We conclude by arguing that assessment can be seen as a movement of avaliar se avaliando, a practice characterized by the reflexivity of teachers and students throughout the process.